A motivação de alunos na preparação e demonstração de experimentos para a divulgação de química: um olhar a partir da teoria da autodeterminação - Faitanini, Beatriz Derisso (2018)
This research had as its main objective the study of the motivational profile of students from the first year of High School in a private school of São Carlos during the completion of a choice process, preparation and demonstration of experimental practices of Chemistry. For understanding of the motivation in the school context it was used as a theoretical reference the Self-Determination Theory, outlining six motivational levels which an individual may present, proposing a self-determination continuum of self-determination. To collect data two questionnaires were used, an open-ended and the other using the Likert scale, applied before and after the completion of a process, and the meetings filming. The open-ended questionnaire aimed to evaluate the satisfaction of the basic psychological needs of the students during the research; the questionnaire using the Likert scale aimed to obtain the students' motivational profile. The data analysis showed that before the implementation of this project the students had higher MR values for the Integrated Regulation and lower for the less self-determined motivational forms. After the project was carried out, the MR values for Integrated Regulation and Intrinsic Motivation increased even more, while the values for less self-determined forms, such as amotivation, decreased, showing that there were – in reference of learning motives - a significant variation in the students' motivational profile. The individual analysis of the students showed that there was a significant change in the motivational orientation of three students, while the others remained with the same motivational orientation, mainly because they were students who declared themselves motivated to study Chemistry even before the implementation of the project. We also observed that the data provided elements that confirm that the occurrence of situations that favor the satisfaction of the basic psychological needs brings the enthusiasm of the students in situations considered favorable to the promotion of intrinsic motivation. Thus, the data collection instruments showed themselves as adequate for the objectives of this work, but it is still important to continue research on the motivation of students in chemistry classes, mainly to understand how the satisfaction of basic needs can influence this change of motivational profile and what factors influence the satisfaction of these needs.